Everyday Life Situations of School-Aged Children with Severe Disabilities: What are the Goals for the Future? An Exploratory Study - Adolfsson, Margareta; Westerberg, Christina; Möller, Kerstin (Journal of Intellectual Disability - Diagnosis and Treatment, 2014)
This study investigated present and future everyday life situations (ELS) in home, school, work, and leisure environments for a group of school-aged children with severe disabilities, including complex disorders and a combination of disabilities. The purpose was to explore universal ELS; clarify how the children can be supported in their development of autonomy; and to gather information on potential overall goals for interventions. To make data comparable, all reported ELS were linked to the International Classification of Functioning, Disability and Health, Child and Youth version (ICF-CY) and listed along with information on the setting. Both today, and in the future, recreational activities and participation in school or work were of highest importance, but few reported ELS involved directly interacting with other children. More ELS were predicted to occur outside the home and with a higher degree of autonomy. Therefore, interventions would be focused on the overall goal that children with severe disabilities take initiatives to become independent and to form relationships with others.